2018
DOI: 10.3390/met8020109
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Microstructures and Tensile Properties after Various Cold Rolling Reductions in AISI 301LN Steel

Abstract: Heavy cold rolling is generally required for efficient grain size refinement in the martensitic reversion process, which is, however, not desirable in practical processing. In the present work, the influence of cold rolling reductions of 32%, 45% and 63% on the microstructure evolution and mechanical properties of a metastable austenitic AISI 301LN type steel were investigated in detail adopting scanning electron microscopy with the electron backscatter diffraction method and mechanical testing. A completely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 34 publications
4
31
1
Order By: Relevance
“…It is possible that some deformed retained austenite (RA) remain in the microstructure as shown in Fig. 12, which affects the microstructural evolution during annealing stage [3,45,47,104,106,111,161,[193][194][195][196][197][198][199]. Moreover, the deformationinduced martensite forms gradually and will be inevitably deformed to different degrees, which also has an influence on microstructure heterogeneity and thereby on the mechanical properties [2,53].…”
Section: Martensite Process and Reversion Annealingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that some deformed retained austenite (RA) remain in the microstructure as shown in Fig. 12, which affects the microstructural evolution during annealing stage [3,45,47,104,106,111,161,[193][194][195][196][197][198][199]. Moreover, the deformationinduced martensite forms gradually and will be inevitably deformed to different degrees, which also has an influence on microstructure heterogeneity and thereby on the mechanical properties [2,53].…”
Section: Martensite Process and Reversion Annealingmentioning
confidence: 99%
“…Regarding the metastability in Fe-Cr-Ni alloys, when Ni + 0.35Cr < 16 wt%, it has been reported that over 90 vol% α'-martensite forms by 90% cold rolling at room temperature [40]. Promisingly, for instance for a 301LN grade, cold-rolling reductions as low as 35-52% seemed to result in excellent strength-ductility combinations, even though the grain size refinement was not most efficient and the obtained grain size was not uniform [2,196,197].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of proper parameters of this thermomechanical treatment, namely the level of cold deformation and temperature and time of reversion annealing can lead up to ultrafinegrained (UFG) microstructure with an excellent combination of high strength and good ductility -see e.g. [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Weidner et al reported a similar orientation in high‐alloy metastable austenitic CrMnNi steel with different nickel contents for cold rolling of less than 70%. A recent study by Järvenpää et al illustrated that the {110}<112> Brass component is the most resistant to a transform in martensite, whereas grains with an orientation between {100}<uvw> and {111}<uvw> show the first α ′‐martensite after a 7% tensile strain.…”
Section: Discussionmentioning
confidence: 99%